PENGARUH FASILITAS KERJA, KOMPENSASI, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA TEGAL - Riska Dwi Arifah; Nur Khojin; Nur Aisyah (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to examine the influence of work facilities, compensation and work motivation variables on the performance of Tegal City education and culture service employees. The method in this research is to strengthen quantitative research methods. with multiple linear regression analysis method. The research sample consisted of 71 employees of the Tegal City Education and Culture Department who were selected using a saturated sample. Data collection methods use questionnaires and interviews. Data processing techniques in research use SPSS (Statistical Package For The Social Scientists). Based on the results of the analysis, this research shows that the work facilities variable has a positive and significant influence on employee performance (t = 1,999> t table = 1,996, sig = 0.050 ≤ 0.05). Compensation also has a positive and significant effect on employee performance (t = 3,964 > t table = 1.996, sig = 0.000 < 0.05). Meanwhile, the work motivation variable shows a positive and significant influence on service quality (t count = 2,678> t table = 1.996, sig = 0.009 < 0.05). Simultaneously, these three variables have a significant effect on service quality, with a calculated F value of 12,176 which is greater than the F table of 2.742 (sig = 0.000 < 0.05).